From traditional interorganisational systems to cloud-based solutions: The impact on supply chain flexibility. Issue 4 (2nd October 2018) - Kopanaki, Evangelia; Karvela, Panagiota; Georgopoulos, Nikolaos
ABSTRACT: The fast changing business environment and the intensive market competition forces firms to adjust and remodel their business strategy continuously. As a solution, firms seek flexibility, not only internally but also at the level of their supply chain. To accomplish this, companies invest in information technology (IT), aiming to improve their business processes and collaboration with trading partners. As previous research supports, the use of IT combined with agile supply chain management improves business performance and offers sustainable competitive advantage. However, the extent to which IT enables and supports supply chain flexibility is still debatable and warrants investigation. Although contemporary Internet-based systems (web-based platforms and cloud-based solutions) seem to overcome the rigidity and inflexibility of traditional interorganisational systems (IOS), they are still associated with issues of interoperability and incompatibility. Although they facilitate supply chain collaboration, by providing access to all stakeholders and enabling information-sharing, they may often lead to closed networks of collaboration. To examine these issues, this paper primarily aims to clarify the notion of flexibility at the level of the supply chain. It also aims to contribute to the process by which organisations effectively evaluate and prioritise competing IT investments. Taking into consideration the multidimensional nature of flexibility, this paper proposes a conceptual framework of supply chain flexibility, distinguishing between the operational, structural, and strategic levels of flexibility. It then uses this framework to explain the impact of IT infrastructures (specifically comprising traditional IOS, web-based collaboration platforms and cloud-based solutions) on the various levels of flexibility. Based on previous research, it identifies specific IT characteristics and provides an approach through which practitioners and researchers can compare different technologies and analyse their benefits and limitations, in terms of supply chain flexibility.